2022
DOI: 10.3390/ijerph19137629
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Quantitative Instrument to Elicit Patient Preferences for Person-Centered Dementia Care Stage 1: A Formative Qualitative Study to Identify Patient Relevant Criteria for Experimental Design of an Analytic Hierarchy Process

Abstract: Person-centered care (PCC) requires knowledge about patient preferences. This formative qualitative study aimed to identify (sub)criteria of PCC for the design of a quantitative, choice-based instrument to elicit patient preferences for person-centered dementia care. Method: Interviews were conducted with n = 2 dementia care managers, n = 10 People living with Dementia (PlwD), and n = 3 caregivers (CGs), which followed a semi-structured interview guide including a card game with PCC criteria identified from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 77 publications
2
16
0
Order By: Relevance
“…During the previous qualitative interviews [ 31 ], we experienced some PlwD to be nervous, as some expected a test and wanted to “perform well”, cf. Supplementary Materials File S1 , row 1, which was confirmed by EP1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…During the previous qualitative interviews [ 31 ], we experienced some PlwD to be nervous, as some expected a test and wanted to “perform well”, cf. Supplementary Materials File S1 , row 1, which was confirmed by EP1.…”
Section: Resultsmentioning
confidence: 99%
“…The overarching AHP study ‘PreDemCare’ [ 37 , 38 ] adopts a sequential mixed-methods design [ 39 ] for final instrument development. Details about the PreDemCare study can be found in [ 37 , 38 ], and a process outline is provided by Mohr et al [ 31 ]. Based on findings from a previous systematic review [ 40 ], stage 1 of the pre-study, including a small expert panel and qualitative interviews [ 31 ], was conducted to identify relevant (sub)criteria of PCC to develop an AHP hierarchy of relevance to (future) decision makers.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations